STRATEGI GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SDN 59 BONTO TENGNGA KEC. CAMBA, KAB. MAROS, SULAWESI SELATAN - Annisa Ashlihatul Akbar; Bunyamin, Andi; Mahmud, M. Hasibuddin; Syahid, Akhmad; Rosmiati; Akil, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Annisa Ashlihatul Akbar. PAI Teachers' Strategies in Increasing Students' Learning Motivation at SDN 59 Bonto Tengnga, Camba District, Maros Regency, South Sulawesi(supervised by Dr. H. Andi Bunyamin, M.Pd and Dr. H. M. Hasibuddin Mahmud, SS., MA). The learning of Islamic Religious Education cannot be separated from the motivation in learning it. An educator is expected to have as many learning strategies as possible that can inspire students to learn fun and to achieve the desired educational goals. Educators must be good at choosing and using the strategies to be used. An educator must be able to provide the best possible motivation to learn to students. This study aims to: Analyzing strategies in increasing students' learning motivation at SDN 59 Bonto Tengnga Camba District, Maros Regency, South Sulawesi. The research method used is a descriptive Qualitative Method with a case study approach. Data was collected through observation, interviews and documentation. Technical data analysis is in the form of data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the PAI teachers' strategies in increasing the learning motivation of students at SDN 59 Bonto Tengnga use expository and contextual learning strategies. Expository strategies are used selectively to provide a clear basic understanding while contextual strategies relate PAI material to students' daily lives. In addition, PAI teachers also implement ice breaking, awarding, and classroom management that support the creation of a conducive learning atmosphere. The effectiveness of the learning strategy can be seen from the fulfillment of learning motivation indicators, namely the desire and desire to succeed, interesting learning activities, a conducive learning environment, and the existence of rewards in learning and supported by an improvement in learning outcomes. Although there are still several obstacles such as limited time, facilities, and differences in student characteristics, in general, the learning strategies implemented by PAI teachers at SDN 59 Bonto Tengnga are considered effective in increasing students' motivation to learn.